Surgical site infections after trauma laparotomy: An observational study from a major trauma center in Saudi Arabia - Chowdhury, Sharfuddin (Saudi Med J, 2019)
OBJECTIVES: To determine the incidence of surgical site infection (SSI) after trauma laparotomy and evaluate variables on presentation to the emergency department (ED) associated with the development of SSI. METHODS: A retrospective cohort study was undertaken of patients presenting directly from the scene who underwent trauma laparotomy between January 2016 and December 2017. The primary outcome variable was SSI, as defined by the Centers for Disease Control and Prevention guideline. A univariate assessment with demographics, vital signs, and acute management was reported. RESULTS: A total of 70 patients were included for data analysis. Of these, 9 (12.9%; 95% confidence interval (CI): 6.9-22.7%) patients developed SSI, including 5 patients with bowel injury (small bowel; n=3, colonic injuries; n=2). Most cases were diagnosed after 7 days in the hospital. All patients developed superficial incisional (skin and subcutaneous tissue) SSI. No predetermined variables, including bowel injury (p=0.08) or duration of surgery (p=0.09), demonstrated a statistically significant association with the development of SSI. CONCLUSION: Rates of SSI after trauma laparotomy were similar to previous reports from other centers. Surgical site infection after trauma laparotomy was diagnosed at a delayed time point after surgery, and patient demographics, injury characteristics, and acute surgical management did not appear to be associated with subsequent diagnosis of SSI.